Polemik Work From Home (WFH) Bagi Perempuan Bekerja di Tengah Digitalisasi Teknologi dan Pandemi - Putri, Sukma Ari Ragil; Fahrudin, Ahmad (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
Abstract: Social distancing are a form of policy that made by the government in order to prevent the spread of the COVID-19 virus. This method, that was made by Indonesian government has implications for the method of working in the pandemic era, namely working from home. The application of social distancing then causes an increase in household activities that increase women's responsibilities in parenting and household work. Through the concept of symbolic violence, this article tries to explain the impact of social distancing restrictions on working women. This article finds that symbolic violence occurs through habitus that shapes women's mindsets so that they feel that caregiving and household work are women's responsibilities. This article also finds various gender inequalities that are increasingly visible with the social distancing restrictions that implemented by Indonesian governement. Keywords: Gender; pandemic; symbolic violence Abstrak: Pembatasan jarak sosial menjadi salah satu kebijakan yang dilakukan oleh pemerintah untuk mencegah persebaran COVID-19. Metode ini dijalankan di Indonesia yang berimplikasi pada metode bekerja era pandemi yaitu work from home atau bekerja dari rumah. Penerapan social distancing kemudian menyebabkan bertambahkan kegiatan rumah tangga yang memperbesar tanggung jawab perempuan dalam kerja pengasuhan dan kerja rumah tangga. Melalui konsep kekerasan simbolik artikel ini mencoba memaparkan dampak dari pembatasan jarak sosial pada perempuan bekerja. Artikel ini menemukan bahwa kekerasan simbolik terjadi melalui habitus yang menyusun pola pikir perempuan sehingga merasa kerja pengasuhan dan kerja rumah tangga merupakan tanggung jawab perempuan. Artikel ini juga menemukan berbagai ketimpangan gender yang semakin terlihat dengan adanya pembatasan jarak sosial yang dilakukan di Indonesia. Kata kunci: Gender; kekerasan simbolik; pandemi